ANALISIS PERPUTARAN PIUTANG DALAM MENINGKATKAN PEROLEHAN LABA BERSIH PADA PT. TERUSAN INDAH PERKASA MEDAN - Farika Amalia Br. Harahap; Dewi Wahyuni; Allia Irmadhani (Worksheet : Jurnal Akuntansi, 2023)
The purpose of this research is to find out and analyze why the company's net profit is not optimal. Theresearch uses data collection techniques, namely interviews, observation and documentation studies.The data analysis technique is descriptive analysis method. The results of this study indicate that theincrease and decrease in the amount of net profit experienced by the company is caused by severalfactors, namely the ups and downs of the number of units sold and the selling price per unit, fluctuationsin the cost of revenue, fluctuations in variable production costs and operating efficiency which areinfluenced by the amount units sold, fluctuations in the value of financial ratios, fluctuations in incomeitems by variations in the number of units sold. In addition, the net profit in 2021 has increased,accompanied by the company's net profit which has increased quite high, this shows that the company'sprofit generated is greater than in the previous year owned by the company so there is no risk of loss inthe coming year. probably won't happen. Furthermore, if the receivables turnover rate is high, the saleslevel will be high, so that revenue can increase and operating profit will also increase. If the profitgrowth rate is low, it means that the sales level is also low, so that revenue will decrease and this willlead to a decrease in operating profit earned due to additional costs that must be incurred by thecompany, such as maintenance costs and inventory storage costs and vice versa.